Pediatric mature B-cell NHL, early referral and supportive care problems in a developing country. Issue 1 (1st January 2019) - Gaytan-Morales, Felix; Alejo-Gonzalez, Francisco; Reyes-Lopez, Alfonso; Palomo, Miguel; Rodriguez-Romo, Laura; Villareal-Martínez, Laura; Sandoval-González, Adriana; Lopez-Facundo, Aracely; Tejocote-Romero, Isidoro; Cárdenas-Cardos, Rocio; Aguilar-Ortiz, Marco; Arreguin-Gonzalez, Farina; et al.
ABSTRACT: Objective: Mature B-cell non-Hodgkin lymphoma (B-NHL) comprises more than 50% of all non-Hodgkin lymphoma (NHL) in children and adolescents. An official report published by the Mexican National Center for the Control and Prevention of Cancer in the Pediatric and Adolescent Populations, reported a lymphoma OS of 71% (including all Hodgkin and NHL). The Mexican Association of Pediatric Oncology and Hematology conducted a retrospective study to analyze the clinical characteristics and outcomes of children with diagnosis of B-NHL in Mexico, in order to perceive the main areas of improvement in the health care. Methods: From 1 January 2000 to 31 December 2016, 166 pediatric patients were diagnosed with B-cell NHL at the participant institutions. Results: According to histology the outcomes were 5-year EFS 63%, for BL/BLL, and 80% DLBCL, ( P = .051), 5-year PFS 81%, for BL/BLL, and 91% for DLBCL, ( P = .126), and 5-year OS 71%, for BL/BLL, and 83% for DLBCL, ( P = .095). Discussion: Overall, 18 patients died due to acute treatment toxicity, resulting in a cumulative incidence of toxic death of 10.84% and an early death rate of 7.23%, defined as <30 days after initial treatment. In conclusion, there is an urgent need to establish an academic collaboration to create strategies to improve pediatric cancer care according to our resources, especially in diseases with expected excellent prognosis as B-NHL. These strategies must include comprehensive supportive care, early referral, and the creation of easy communication between pediatric and adults centers as well as late-effects clinics.